Pengaruh peran serta lingkungan ekologi belajar dan tingkat perkembangan diri siswa terhadap motivasi belajar Siswa Sekolah Dasar di Kecamatan Nalumsari Kabupaten Jepara - Anni Masudah (IKIP Siliwangi, 2023)
This study aims to analyze the influence of the role of the ecological learning environment and the level of students' self-development on the learning motivation of elementary school students in Nalumsari District, Jepara Regency. This study uses a correlational quantitative approach. The object of the research includes three public elementary schools consisting of SDN 2 Bendanpete, SDN 1 Ngetuk and SDN 1 Bategede. The research subjects included students and their guardians from the three state elementary schools which had a population of 632 students and the sampling method used was the Slovin technique (n=87). Data collection techniques used the method of observation, documentation and questionnaires. Data analysis technique with regression analysis with SPSS. The results showed that partially the ecological learning environment had a significant positive effect on students' learning motivation. Likewise, student self-development has a significant positive effect on student learning motivation partially. The results of multiple linear regression showed that the coefficient value for the student's learning ecological environment variable had a significant negative effect on the student's learning motivation variable, while the student's level of self-development variable had a significant positive effect on the learning motivation variable.Â